Application of response surface methodology for heterogeneous catalytic removal of paracetamol by OMS-2/persulfate - Tunc, Zeynep; Tepe, Ozlem (Elsevier Science Inc, 2022)
In this study, paracetamol removal by OMS-2 (manganese oxide octahedral molecular sieves) as a novel catalyst and persulfate (PS) was investigated. The response surface methodology was used to model paracetamol removal, optimize operational parameters, and determine the impact of operational parameters. OMS-2 amount, persulfate concentration and paracetamol concentration were chosen as operational parameters in central composite design technique. The level of OMS-2 was between 0.025 and 0.50 g/L, while persulfate and paracetamol levels were 0.50-10.00 g/L and 5.00-250.00 mg/L, respectively. The influence of these three independent variables on paracetamol removal was evaluated using ANOVA. According to the results of variance analysis (ANOVA), the quadratic model was statistically significant (P < 0.0001), and the determination coefficient value (R-2: 0.9662) was high. The high coefficient of determination of the quadratic model showed that the experimental results fit well with the predicted results, that is, the model was valid for predicting the experimental results. Each independent variable was effective. The desirability function demonstrated that optimum conditions were OMS-2 amount of 0.40 g/L, persulfate concentration of 5.93 g/L, and paracetamol concentration of 54.66 mg/L for maximum paracetamol removal. The OMS-2/PS system exhibited excellent catalytic performance for paracetamol removal.
Keywords: OMS-2; Optimization; Paracetamol; Persulfate; Response surface methodology